Clinical outcomes and timing on the combination of focal radiation therapy and immunotherapy for the treatment of brain metastases - Antelo, Gabriela; Comas, Silvia; Casas, Francesc; Valduvieco, Izaskun; Barreto, Tanny; Laplana, María; Mases, Joel; Oses, Gabriela; Mollà, Meritxell (Frontiers in Immunology, 2023)
Introduction: Radiotherapy is one of the standard treatments for brain metastases (BM).Over the past years, the introduction of immunotherapy as routine treatment for solid tumors has forced investigators to review and evaluate how it would interact with radiation.Radiation and Immunotherapy have shown a synergic effect activating the host's immune system and enhancing treatment response. The combinatory effect on BM is currently under investigation.Methods: Data published on Pubmed to determine toxicity, survival, treatment characteristics and timing on the combination of radiotherapy and immunotherapy for the treatment of BM has been reviewed.Mostly retrospective reviews report an improvement of intracranial progression free survival (iPFS) when combining radioimmunotherapy for BM patients. Two systematic reviews and meta-analysis and one phase II prospective trial also report a benefit on iPFS without an increase of toxicity. Among the published literature, the definition of concurrency is heterogeneous, being one month or even narrowed intervals correlated to better clinical outcomes. Toxicity due to concurrent radioimmunotherapy, specifically symptomatic radionecrosis, is also directly analyzed and reported to be low, similar to the toxicity rates secondary to stereotactic radiosurgery alone.Radiation combined with immunotherapy has shown in predominantly retrospective reviews a synergic effect on the treatment of BM. The concurrent combination of radioimmunotherapy is a feasible therapeutic strategy and seems to improve clinical outcomes, especially iPFS, when delivered within <30 days. Larger prospective and randomized studies are needed to establish reliable outcomes, best delivery strategies and toxicity profile.